ANALISIS POPULASI OWA JAWA (Hylobates moloch Audebert 1797) DI KORIDOR TAMAN NASIONAL GUNUNG HALIMUN SALAK - Yumarni .; Hadi Sukadi Alikodra; Lilik Budi Prasetyo; Rinekso Soekmadi (Media Konservasi, 2011)
Javan gibbon (Hylobates moloch Audebert 1797) is an endemic primate of Java Island, living only in West and Central Java. IUCN (International Union for Conservation of Nature) puts it in the list of endangered species. This studi aims at understanding the population of javan gibbon in Gunung Halimun Salak National Park. This research have been done in Gunung Halimun Salak National Park’s Corridor. It employs the line transect method. This study result 9 groups and 28 individuaals of javan gibbon in Gunung Halimun Salak Corridor. The average group density for javan gibbon for the Halimun Salak National Park Corridor was 0,01-0,03 groups/km2, and population density was 0,04-0,09 individuals/km2.The distribution of groups javan gibbon in Sukagalih, Cilodor, GH, Cisarua, Ciherang, and Cipicung but not detection javan gibbon group in Cipanas. Groups composition of adult male and female, subadult, and infant.  Keywords:  javan gibbon,endemic, density, population, corridor